Faktor-Faktor yang Mempengaruhi Keberlanjutan Fiskal Pemerintah Daerah di Indonesia - Hidayat, Mochamad Farhan; Suseno, Deky Aji (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
Fiscal sustainability has become an important issue for local governments as it reflects their ability to finance public services without creating a prolonged deficit burden. Regencies and cities in West Java face challenges of high dependence on central government transfers and imbalances between local revenue and public expenditure. This study aims to analyze the factors influencing fiscal sustainability of regencies and cities in West Java Province. Fiscal sustainability in this study is proxied by the nominal fiscal position (the difference between total regional revenue and total regional expenditure), where a positive value indicates a surplus and a negative value indicates a deficit. This research employs panel data from 27 regencies/cities in West Java during the 2018–2022 period, with independent variables consisting of Local Own-Source Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Regional Expenditure Ratio (RBD), and Gross Regional Domestic Product (GRDP). Data were analyzed using panel regression with the Common Effect Model. The results show that PAD (Prob. = 0.0804), DAK (Prob. = 0.0136), and RBD (Prob. = 0.0004) have a negative and significant effect on fiscal sustainability. In contrast, DAU has a positive and significant effect (Prob. = 0.0463), while GRDP has no significant effect (Prob. = 0.3325). These findings indicate that increases in PAD and DAK tend to encourage greater spending, thereby worsening the fiscal position, consistent with the flypaper effect and fiscal illusion theories. Meanwhile, DAU contributes positively to improving the fiscal position. The results emphasize the need for more disciplined expenditure management so that additional revenues can effectively strengthen local fiscal sustainability.